2015
DOI: 10.3390/su7066412
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Cultural and Sustainable Rural Tourism in a Smart Region: The Case Study of Marmilla in Sardinia (Italy)

Abstract: This paper is being inserted into the current debate on the topic of sustainability, as it applies to rural tourism. In particular, it addresses the need to identify strategic actions that will enhance the dissemination of cultural resources to facilitate cultural planning. Balancing the dynamic tension that characterizes the relationship between tourism development and protection of the landscape is key to finalizing appropriate planning strategies and actions, especially in the context of marginal rural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 26 publications
0
89
0
8
Order By: Relevance
“…For this reason, encouraging sustainable tourism activity can be considered the best practice, for the protection and preservation of the universal value of rural World Heritage Sites over time [45]. Moreover, in rural and marginal areas, Garau (2015) outlined the importance of finding a balance between tourism development and landscape' protection. This author identified strategic actions, such as the application of new information communication technologies that will enhance the dissemination of cultural resources to facilitate cultural planning [46].…”
Section: The Best Practices Strategies Actions and Measures Appliedmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, encouraging sustainable tourism activity can be considered the best practice, for the protection and preservation of the universal value of rural World Heritage Sites over time [45]. Moreover, in rural and marginal areas, Garau (2015) outlined the importance of finding a balance between tourism development and landscape' protection. This author identified strategic actions, such as the application of new information communication technologies that will enhance the dissemination of cultural resources to facilitate cultural planning [46].…”
Section: The Best Practices Strategies Actions and Measures Appliedmentioning
confidence: 99%
“…Moreover, in rural and marginal areas, Garau (2015) outlined the importance of finding a balance between tourism development and landscape' protection. This author identified strategic actions, such as the application of new information communication technologies that will enhance the dissemination of cultural resources to facilitate cultural planning [46]. Recently, Cerutti et al [47] demonstrated that sustainable tourism can support local economies and help to preserve landscape and cultural heritage.…”
Section: The Best Practices Strategies Actions and Measures Appliedmentioning
confidence: 99%
“…A questionnaire was designed as a means for collecting data. The key statements concerning resident perceptions and attitudes were sourced from the existing literature [3,12,48] particularly that relevant to Asian settings [4,49]. Minor contextual amendments were made following discussions with some Indian tourism scholars and practitioners who were asked to judge the relevance of the statements to the Indian context.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…In recent tourism literature, a new phenomenon was found in the behavior of tourists: many tourists prefer "values of experience" to "value for money" [17,18]. Interestingly, the tourist tends to make a choice that may be relatively unplanned and disorganized, if this choice is related to an experience that matches his personal values [16].…”
Section: Tourists' Sustainable Values In Smart Tourismmentioning
confidence: 99%
“…Interestingly, the tourist tends to make a choice that may be relatively unplanned and disorganized, if this choice is related to an experience that matches his personal values [16]. For instance, plenty of tourists make quick tour decisions to have an authentic experience (e.g., social and cultural identities, traditions, memories, food, local peculiarities, and rural landscape) with chances of being involved in various activities to satisfy their own sustainable values [15,17]. This phenomenon suggests that tourists tend to set and expect higher and more diversified values for tourism experience.…”
Section: Tourists' Sustainable Values In Smart Tourismmentioning
confidence: 99%